2018
DOI: 10.1117/1.oe.58.1.011004
|View full text |Cite
|
Sign up to set email alerts
|

Momentum predictability and heat accumulation in laser-based space debris removal

Abstract: Small space debris objects of even a few centimeters can cause severe damage to satellites. Powerful lasers are often proposed for pushing small debris by laser-ablative recoil toward an orbit where atmospheric burn-up yields their remediation. We analyze whether laser-ablative momentum generation is safe and reliable concerning predictability of momentum and accumulation of heat at the target. With hydrodynamic simulations on laser ablation of aluminum as the prevalent debris material, we study laser paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…To consider the dependencies of laser-exerted force from incidence angle and surface properties for different target geometries, the DLR code Examination Program for Irregularly Shaped Debris Targets (Expedit) is used, which combines discretization of laser beam and target surface for parallelized momentum computation. The code had formerly been developed for calculation of laser-imparted momentum in laser ablation and is described in greater detail in [21]. An interaction module for photon pressure had been developed subsequently and is firstly employed in this study.…”
Section: A Laser-matter Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…To consider the dependencies of laser-exerted force from incidence angle and surface properties for different target geometries, the DLR code Examination Program for Irregularly Shaped Debris Targets (Expedit) is used, which combines discretization of laser beam and target surface for parallelized momentum computation. The code had formerly been developed for calculation of laser-imparted momentum in laser ablation and is described in greater detail in [21]. An interaction module for photon pressure had been developed subsequently and is firstly employed in this study.…”
Section: A Laser-matter Interactionmentioning
confidence: 99%
“…Finally, the debris fragment population has been generated by a statistical approach using an estimate of A cs from DISCOS data on A rcs and generating a statistical distribution of axis ratios X /Y and Y /Z in agreement with the fragment statistics from ground-based satellite crash tests [22]; cf. [21] for more details on this method. An overview on shapes and axis ratios for all 9101 OOR targets is given in Fig.…”
Section: A Laser-matter Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research has been dedicated to the study of the feasiblity of space debris removal using pulsed laser beams [1][2][3][4] and have all shown that the understanding of the processes governing the laser-target interaction as well as plasma formation and expansion is crucial for an effective debris removal.…”
Section: Introductionmentioning
confidence: 99%
“…Extension of non-equilibrium modeling of metal ablation to the thermal effects inside the target material using a two temperature model Amina Ait oumeziane (1) and Jean-Denis Parisse (2), (3) (1) Centre RAPSODEE UMR CNRS 5302, IMT mines Albi-Carmaux, France.…”
mentioning
confidence: 99%